UN Interventions: The Role of Geography - Juan Carlos Duque; Michael Jetter; Santiago Sosa (Institute for the Study of Labor (IZA), 2014)
This paper argues that UN military interventions are geographically biased. For every 1,000 kilometers of distance from the three Western permanent UNSC members (France, UK, US), the probability of a UN military intervention decreases by 4 percent. We are able to rule out several alternative explanations for the distance finding, such as differences by continent, colonial origin, bilateral trade relationships, foreign aid flows, political regime forms, or the characteristics of the Cold War. We do not observe this geographical bias for non-military interventions and find evidence that practical considerations could be important factors for UNSC decisions to intervene militarily.
Keywords: D74; F52; F53; N40; R12; 330; United Nations; conflict resolution; international organizations